2016
DOI: 10.1186/s12870-016-0913-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of eleven monosomic alien addition lines added from Gossypium anomalum to Gossypium hirsutum using improved GISH and SSR markers

Abstract: Background Gossypium anomalum (BB genome) possesses the desirable characteristics of drought tolerance, resistance to diseases and insect pests, and the potential for high quality fibers. However, it is difficult to transfer the genes associated with these desirable traits into cultivated cotton (G. hirsutum, AADD genome). Monosomic alien addition lines (MAALs) can be used as a bridge to transfer desired genes from wild species into G. hirsutum. In cotton, however, the high number and smaller size of the chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…To date, there has been no report of the construction of a complete set of MAALs for diploid and tetraploid populations of Gossypium. In a previous study, MAALs covering Developing monosomic alien addition lines from G. anomalum Breeding Science Preview BS 11 G. anomalum chromosomes were developed in the cotton genotype TM-1 background (Wang et al 2016). In the present study, we developed a complete set of MAALs from G. anomalum chromosomes in the background of the cotton variety Su8289, which comprehensively shows good performance and makes a suitable recipient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, there has been no report of the construction of a complete set of MAALs for diploid and tetraploid populations of Gossypium. In a previous study, MAALs covering Developing monosomic alien addition lines from G. anomalum Breeding Science Preview BS 11 G. anomalum chromosomes were developed in the cotton genotype TM-1 background (Wang et al 2016). In the present study, we developed a complete set of MAALs from G. anomalum chromosomes in the background of the cotton variety Su8289, which comprehensively shows good performance and makes a suitable recipient.…”
Section: Discussionmentioning
confidence: 99%
“…MAALs in the genetic background of Upland cotton have been obtained from a number of diploid Gossypium species such as G. anomalum ( Wang et al 2016 ), G. sturtianum (CC) ( Rooney et al 1991 ), G. somalense (E 2 E 2 ) ( Zhou et al 2004 ) and G. australe (G 2 G 2 ) ( Sarr et al 2011 ). It is, however, difficult to construct a whole set of diploid cotton MAALs due to the instability of alien chromosomes and time-consuming identification processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is necessary to point out that until now, only two sets of chromosome alien addition lines in cotton had been developed by our lab [ 5 , 27 ]. Here, from the M 1 generation, we also found that 44 individuals were monosomic alien additions that involved 12 chromosomes (all except chromosome 13G).…”
Section: Discussionmentioning
confidence: 99%
“…MAALs, on the other hand, are pre-breeding lines that carry an additional chromosome from the wild donor alongside the full chromosome complement of the cultivated, recipient parent (2 n + 1) (Khush 2010 ). This distinctive feature of MAALs makes them highly suitable for assigning alien traits to specific chromosomes of the wild donor, dissecting wild genomes into individual chromosome entities in a functional genomic background, and identifying novel genes underlying traits of agronomic importance (Khush 2010 ; Wang et al 2016 ; Narain et al 2016 ). For introgressive breeding applications, however, the utilization of MAALs is largely restricted by the unstable transmission of the additional chromosome, as well as the potential loss of chromosome integrity due to homeologous recombinations (Miller and Tanksley 1990 ; Chetelat et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%